The Validity of Student Worksheet Using Inquiry-Based Learning Model with Science Process Skill Approach for Physics Learning of High School - Yulkifli Yulkifli; Melia Vivi Ningrum; Widyaningrum Indrasari (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2019)
The significant influence of the 21st century brought a change in Physics learning. Students are required to have the skills to think, work, and live in the surrounding environment. To achieve 21st-century skills needed teaching materials that can support the learning process.With the presence of teaching materials, students are more active in building their knowledge and easy to understand the material provided. Teaching materials that can guide students with a productive task to practice is the student worksheet. A student worksheet is a teaching material that contains a set of activities to maximize students understanding in achievement of competence. To improve the competence of students, one of the efforts that teachers to develop quality student worksheet. A student worksheet is considered qualified if has validity criteria. The validity assessment of the student worksheet is carried out by expert reviews. This research aims to determine the validity of the student worksheet using an inquiry-based learning model with a science process skills approach. The research conducted is design research using the Plomp model with the type of development studies, where validity is at the stage of development. The research instrument used a validity questionnaire to be filled by expert reviews, then analyzed using Aiken's V formula. The result of the validity showed that the student worksheet using an inquiry-based learning model with a science process skills approach having valid criteria with a value of 0.88. It means that the student worksheet is decent for use in Physics learning.